PERAN BUDAYA ORGANISASI DALAM MEMODERASI PENGARUH KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN : STUDI PADA KARYAWAN CLEANING SERVICE PT. ISS INDONESIA - VELEN, LAURENSIA (Kajian Ilmiah Mahasiswa Manajemen, 2012)
This research aims to determine the role of organizational culture in moderating the influence of organizational commitment on employee performance of cleaning service PT. ISS Indonesia Surabaya. The number of samples used is 150 samples. The data analysis technique used is a regression moderation with SPSS 16.0 program. The research result shows that organizational commitment has a positive effect on employee performance of the cleaning service PT. ISS Indonesia, while organizational culture does not moderate the influence of organizational commitment on employee performance so that the relationship is weak or in other words, organizational culture is not a moderating variable.